INFORMATION AND COMMUNICATION TECHNOLOGY AND STUDENTS WITH DISABILITIES - Bekteshi, Luan (European Scientific Journal, ESJ, 2015)
The purpose of this research study was to identify the problems encountered by persons with physical disabilities to attend full-time studies at the University "Alexander Xhuvani" Elbasan. In addition, it serves to highlight the obstacles in the university environment and to provide adequate information for decision-makers at the university in order for them to be able to recognize such barriers and to carefully consider and plan the inclusion of individuals with physical disabilities in university. Subject for this study were a group of 22 students with physical disabilities, 14 (fourteen) of whom were male and 8 (eight) were female. All these students who were contacted directly have identified difficulties in benefiting applications in the information system of the university, elearning, web-site navigability, and downloading various documents from the system etc. This paper also gives some suggestions about improvements that should be made to the information system in the university, in order to be used efficiently by persons with disabilities, academically as well as administratively.